(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to compare the marketing mix of the Siomai Food Stalls and Siomai Food carts in terms of price, product, place, and promotions. The results of this study reveal that the majority of the respondents of Siomai Food Stalls and Siomai Food Carts are aged 18-23 years old; a bachelor`s degree is the highest educational attainment. Then, their assessment of the marketing mix in terms of price, product, and place are strongly agreed aside from promotion, and there is no significant difference between the assessment of the marketing Mix of Food Stall and Food Cart Siomai Businesses in terms of place, price, and promotion; there is a significant difference between and among the assessment on the marketing Mix of Food Stall and Food Cart Siomai Businesses in terms of place, price, product, and promotion and there are recommendations to proposed to enhance more on their marketing mix. This study recommended that Siomai businesses need to market their businesses to the ages of 24-29 years old, and the Siomai Food Stalls and Siomai Food Carts must stay on what they are practicing when it comes to being convenient and easy to reach by the customers and must focus on their promotions and advertisement in their businesses.